2016
DOI: 10.1177/1012690216636607
|View full text |Cite
|
Sign up to set email alerts
|

Sports and structured leisure as sites of victimization for children and young people in Finland: Looking at the significance of gender and ethnicity

Abstract: Availability and access have been central worries that are discussed related to children's and young people's sport and other structured leisure activities. In this article, we shift the focus towards children's and young people's experiences of violence perpetrated by coaches or leaders within such activities in Finland. We use a large-scale survey on children's and young people's experiences of violence in different spheres of life (Finnish Child Victim Survey 2013) as the data, and concentrate on the signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…This kind of situation in sport is prevailing and manifests itself year after year. As Stirling [19] revealed in 2013, coaches themselves stated that they had repeatedly experienced offending behavior from their coaches in the past, while most of the athletes still today treated such behavior of the coach as an obligatory part of their work [14]. Thus, reticence and hiding of the negative information are beneficial for both aggressors and coaches worrying about their authority.…”
Section: Figure 1 Matrix Of Nine Vectorsmentioning
confidence: 99%
“…This kind of situation in sport is prevailing and manifests itself year after year. As Stirling [19] revealed in 2013, coaches themselves stated that they had repeatedly experienced offending behavior from their coaches in the past, while most of the athletes still today treated such behavior of the coach as an obligatory part of their work [14]. Thus, reticence and hiding of the negative information are beneficial for both aggressors and coaches worrying about their authority.…”
Section: Figure 1 Matrix Of Nine Vectorsmentioning
confidence: 99%
“…Competition becomes one of the incentives for emotional abuse (Gervis et al, 2016), which relates to the approach that antisocial and aggressive behaviour in sport is simply a must in order to achieve results (Stirling and Kerr, 2014). Seeking victories and the development of psychologically strong athletes, coaches do not avoid shouting at them, shoving, hitting them (Narwal, 2014;Peltola and Kivijärvi, 2017), and athletes interacting with weaker team members or those who have lower-level sports mastery do not shy away from sneering at them (Steinfeldt et al, 2012). Therefore, negative interrelationships in sport between peers, coaches and parents (Enoksen, 2011;Hassan et al, 2017) can be considered quite an important cause of quitting organized sport among children and young people.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies analysing key determinants of drop out of sport also distinguish behavior of coaches and teammates ( Fraser-Thomas et al, 2008 ; Hassan et al, 2017 ). Seeking victories and educating psychologically strong athletes, coaches do not avoid shouting, shoving, hitting them ( Narwal, 2014 ; Peltola and Kivijärvi, 2017 ), while athletes interacting with teammates who are weaker or whose sports mastery is lower do not shy away to mock at them ( Steinfeldt et al, 2012 ). This trend is also particularly supported by the approach that negative behavior in sport is simply mandatory in order to achieve results ( Stirling and Kerr, 2014 ), and often it takes the form of bullying ( Fisher and Dzikus, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tamminen et al (2013) , who investigated the situation among elite female athletes, found that bullying victimization from teammates was observed in sport. Other studies disclose not only peer bullying, but also draw attention to the coach as a bully ( Cense and Brackenridge, 2001 ; Peltola and Kivijärvi, 2017 ), while relational aggression is the most frequently reported form of bullying ( Kerr et al, 2016 ). Hence, bullying can acquire not only horizontal (athlete-athlete) but also vertical (coach-athlete) character.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation